Structure and meaning in the third vision of Amos (7:7-17) - Campos, Martha E. (2011)
This article argues that meaning in Amos’s third vision is encoded in its structure and poetics. The dynamic of a chiasm in vv 11c–17 simulates the vision’s object and metaphor: the tin wall. Built on concepts from Kings and Jeremiah, the whole text is deuteronomistic. A variety of known difficulties in Amos 7:7–17 are addressed (e.g., the solution to the wordplay, Amos’s denial, the anomaly of the Amaziah narrative, the lack of reference to Assyria, and Jeroboam’s relationship to the sword).
Keywords: Bibel